Maritime Activities and Energy Security: Contemporary Challenges and Multifaceted Interactions - Ківалов, Сергій Васильович; Ківалов, С. В.; Kivalov, Serhii V. (Odesa : Publishing House Helvetica, 2025)
This article explores how maritime, and port activities underpin energy security at national, regional, and global levels. It identifies key factors – legal (regulatory), environmental, geo-economic, and technological – that shape these contributions. The article also notes that shifting climate, military, political, and economic challenges are influencing energy security strategies. The maritime dimension of energy security goes beyond just safeguarding maritime transport of energy resources; it also includes protecting all infrastructure involved in maritime energy supply chains. Additionally, offshore green energy is becoming increasingly significant. The focus is on evidence from Baltic, Black Sea, and Middle East regions.
Kivalov S. Maritime Activities and Energy Security: Contemporary Challenges and Multifaceted Interactions / S. Kivalov // Lex Portus. - Odesa : Publishing House Helvetica, 2025. - 11(4). - Р. 23–33. URL: https://doi.org/10.62821/lp11402
Keywords: maritime and port activities; maritime supply chains; energy resources; climate change; modern wars; alternative and traditional energy